Effect of Nb and F Co-doping on Li1.2Mn0.54Ni0.13Co0.13O2 Cathode Material for High-Performance Lithium-Ion Batteries - Ming, Lei; Zhang, Bao; Cao, Yang; Zhang, Jia-Feng; Wang, Chun-Hui; Wang, Xiao-Wei; Li, Hui (Frontiers in Chemistry, 2018)
The Li1.2Mn0.54-xNbxCo0.13Ni0.13O2-6xF6x (x=0, 0.01, 0.03, 0.05) is prepared by traditional solid-phase method, and the Nb and F ions have been successfully doped into Mn and O sites of layered materials Li1.2Mn0.54Co0.13Ni0.13O2, respectively. The incorporating Nb ion in Mn site could effectively restrain the migration of transtion metal ions during long-term cycling, and keep the stability of the crystal structure. The Li1.2Mn0.54-xNbxCo0.13Ni0.13O2-6xF6x shows suppressed voltage fade and higher capacity retention of 98.1 after 200 cycles at rate of 1 C. The replacement of O2- by the strongly electronegative F- was beneficial for suppressed the structure change of Li2MnO3 from the eliminating of oxygen in initial charge process. Therefore, the initial coulomb efficiency of doped Li1.2Mn0.54-xNbxCo0.13Ni0.13O2-6xF6x gets improved, which is higher than that of pure Li1.2Mn0.54Co0.13Ni0.13O2. In addition, the Nb and F co-doping could effectively enhance the transfer of lithium-ion and electrons, and thus improving rate performance.